Combinatorial Coordination Self‐Assembly for Organopalladium Cages with Fine‐Tuned Structure and Function - Tian, Chong‐Bin; Sun, Qing‐Fu (Chemistry : a European journal, 2023)
Discrete organopalladium coordination cages have shown great potential in applications ranging from molecular recognition and sensing, drug delivery to enzymatic catalysis. While many of the known organopalladium cages are homoleptic structures with regular polyhedral shapes and symmetric inner cavities, heteroleptic cages with complex architectures and new functions coming from their anisotropic cavities have received an increasing attention recently. In this concept article, we discuss a powerful combinatorial coordination self‐assembly strategy toward the construction of a family of organopalladium cages, including both homoleptic and heteroleptic ones, from a given library of ligands. Within such a cage family, the heteroleptic cages often feature systematically fine‐tuned structures and emergent properties, distinct from their parent homoleptic counterparts. We hope the concepts and examples provided in this article can offer some rational guidance for the design of new coordination cages toward advanced functions. Combinatorial coordination self‐assembly is a powerful tool to create the lower‐symmetric coordination cages with increasing structural complexities and advanced functions. In this concept article, we define and summarized the strategy for the combinatorial self‐assembled PdII coordination cages. Emergent functions on some selected PdII coordination cages were also introduced with an aim of emphasizing the advantages of the heteroleptic cages.